2020
DOI: 10.1038/s41467-020-18558-7
|View full text |Cite
|
Sign up to set email alerts
|

Cold spells in the Nordic Seas during the early Eocene Greenhouse

Abstract: The early Eocene (c. 56 - 48 million years ago) experienced some of the highest global temperatures in Earth’s history since the Mesozoic, with no polar ice. Reports of contradictory ice-rafted erratics and cold water glendonites in the higher latitudes have been largely dismissed due to ambiguity of the significance of these purported cold-climate indicators. Here we apply clumped isotope paleothermometry to a traditionally qualitative abiotic proxy, glendonite calcite, to generate quantitative temperature es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 80 publications
(166 reference statements)
1
19
0
Order By: Relevance
“…S4). Distinct cold spells around 55 Ma have previously been reported for the North Atlantic region ( 32 ), and the Δ 47 temperatures from ( 18 ) show that these extended to the deep South Atlantic (Fig. 1A, pink stars and blue triangle).…”
supporting
confidence: 64%
“…S4). Distinct cold spells around 55 Ma have previously been reported for the North Atlantic region ( 32 ), and the Δ 47 temperatures from ( 18 ) show that these extended to the deep South Atlantic (Fig. 1A, pink stars and blue triangle).…”
supporting
confidence: 64%
“…Such factors may contribute to the retention of eumelanin in the fossil record by stabilizing it against decay and providing an inherent resistance to diagenetic alteration [89]. Moreover, the relatively mild geothermal conditions of the Stolleklint Clay and Fur Formation [90,91] presumably limited breakdown (previous studies have indicated that elevated burial temperature is a major factor controlling the preservation of eumelanin [92] as well as other molecular components and structures in arthropods [11,61,66,69]).…”
Section: Discussionmentioning
confidence: 99%
“…The ∼1.5°C difference in reconstructed temperature between the calibrations in the low temperature range (<30°C) may seem trivial and requires the complete A. islandica data set (N = 278; see Figure 3) to resolve. However, in paleoclimate reconstructions (e.g., Agterhuis et al, 2022;de Winter, Müller et al, 2021;de Winter et al, 2017;Meckler et al, 2022;Petersen et al, 2016;Vickers, Fernandez, et al, 2020), this temperature offset may have significant consequences. A ∼1.5°C cold bias in temperature reconstructions may lead to a significant underestimation of climate sensitivity to CO 2 forcing, biasing the physical science basis for informing policymakers about future climate change (e.g., Dennis et al, 2013;IPCC, 2021;Modestou et al, 2020;Tierney et al, 2020;Westerhold et al, 2020).…”
Section: Calibrating the Clumped Isotope-temperature Relationship In ...mentioning
confidence: 99%